Formatting portfolio evaluation in islamic education at smp negeri 3 surakarta - Rizky Nur Utami; Anggraini Putri Rahmawati; Faturrohman Majid; Nurul Latifatul Inayati; Agorovi Kuncoro (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2024)
This research aims to find out how portofolio learning is implemented and evaluated at SMP Negeri 3 Surakarta. This research uses a qualitative approach and uses descriptive methods. The tecnique used was an interview with the PAI teacher with the inisials U. The interview was carried out by preparing several questions that were appropriate to this research study and then conveying them to the resouce person. The results of this research show that PAI teachers at SMP Negeri 3 Surakarta have carried out portofolio evaluation activities. The form of portofolio evaluation activities includes practice accoording to the chapter that is the learning material, discussions beteween groups and a portofolio of assignments given. Evaluation is carried out through an assessment rubric that has been created as well as special tasks carried out by PAI teachers namely making a list of prayers and reciting the koran while at home. This is an additional assessment at the end of the semester which can help boost the value of PAI subjects. The obstacles experienced when carrying out portofolio evaluations are students’ negligence in carrying out assignments and constraints in the duration of preparation for PAI practical activities.